Novel sulphur-containing imatinib metabolites found by untargeted LC-HRMS analysis - Vrobel, Ivo; Friedecký, David; Faber, Edgar; Najdekr, Lukáš; Mičová, Kateřina; Karlíková, Radana; Adam, Tomáš (European journal of pharmaceutical sciences, 2017)
Untargeted metabolite profiling using high-resolution mass spectrometry coupled with liquid chromatography (LC-HRMS), followed by data analysis with the Compound Discoverer 2.0™ software, was used to study the metabolism of imatinib in humans with chronic myeloid leukemia. Plasma samples from control (drug-free) and patient (treated with imatinib) groups were analyzed in full-scan mode and the unknown ions occurring only in the patient group were then, as potential imatinib metabolites, subjected to multi-stage fragmentation in order to elucidate their structure. The application of an untargeted approach, as described in this study, enabled the detection of 24 novel structurally unexpected metabolites. Several sulphur-containing compounds, probably originating after the reaction of reactive intermediates of imatinib with endogenous glutathione, were found and annotated as cysteine and cystine adducts. In the proposed mechanism, the cysteine adducts were formed after the rearrangement of piperazine moiety to imidazoline. On the contrary, in vivo S-N exchange occurred in the case of the cystine adducts. In addition, N-O exchange was observed in the collision cell in the course of the fragmentation of the cystine adducts. The presence of sulphur in the cysteine and cystine conjugates was proved by means of ultra-high resolution measurements using Orbitrap Elite. The detection of metabolites derived from glutathione might improve knowledge about the disposition of imatinib towards bioactivation and help to improve understanding of the mechanism of its hepatotoxicity or nephrotoxicity in humans.
Keywords: Chromatography, Liquid; Cysteine; Humans; Tandem Mass Spectrometry; inhibitory proteinkinas; Untargeted metabolite profiling; LC-HRMS; imatinib mesylát; Metabolization; Imatinib Mesylate; Compound Discoverer™; Antineoplastic Agents; lidé; Cystine; cystein; Glutathione; tandemová hmotnostní spektrometrie; Protein Kinase Inhibitors; cystin; chromatografie kapalinová; Sulfur; protinádorové látky; síra; Imatinib